1992
DOI: 10.1172/jci116005
|View full text |Cite
|
Sign up to set email alerts
|

Glucose transport in human skeletal muscle cells in culture. Stimulation by insulin and metformin.

Abstract: Primary human muscle cell cultures were established and the regulation of glucose transport was investigated. Primary cultures were allowed to proceed to the stage of myotubes through fusion of myoblasts or were used for clonal selection based on fusion potential. In clonally selected cultures, hexose (2-deoxyglucose) uptake into myotubes was linear within the time of study and inhibitable by cytochalasin B (IC5o = 400 nM). Cytochalasin B photolabeled a protein(s) of45,000-50,000 D in a D-glucose-protectable m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
106
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(123 citation statements)
references
References 58 publications
15
106
1
Order By: Relevance
“…On the other hand, at the relatively high levels of insulin used in the present clamp studies, hepatic insulin resistance is likely to have been overcome or minimised. In addition, metformin treatment of rats in vivo provokes increases in insulin-stimulated glucose transport, as measured in vitro in isolated muscle strips [11,12], and metformin treatment of L6 myotubes [13] and cultured human myocytes [14] increases glucose transport, in the absence of concurrent insulin treatment. Moreover, we have recently found that metformin, via AMPK, provokes increases in aPKC activity and thereby increases glucose transport even more effectively than insulin in L6 myotubes (Sajan MP, Farese RV, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, at the relatively high levels of insulin used in the present clamp studies, hepatic insulin resistance is likely to have been overcome or minimised. In addition, metformin treatment of rats in vivo provokes increases in insulin-stimulated glucose transport, as measured in vitro in isolated muscle strips [11,12], and metformin treatment of L6 myotubes [13] and cultured human myocytes [14] increases glucose transport, in the absence of concurrent insulin treatment. Moreover, we have recently found that metformin, via AMPK, provokes increases in aPKC activity and thereby increases glucose transport even more effectively than insulin in L6 myotubes (Sajan MP, Farese RV, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…However, particularly with long-term therapy, metformin provokes increases in insulin-stimulated glucose disposal [6][7][8][9][10], presumably at least partly by increasing glucose utilisation in muscle. Moreover, in vivo treatment of rats with metformin provokes increases in insulin-stimulated glucose transport, as measured in isolated skeletal muscle preparations [11,12], and metformin itself increases 2-deoxyglucose uptake in cultured myocytes [13,14]. Thus, metformin-induced increases in basal and/or insulinstimulated glucose transport may contribute to increases in glucose disposal following metformin treatment of diabetic subjects.…”
Section: Introductionmentioning
confidence: 99%
“…In response to insulin stimulation, GLUT4, but not GLUT1, is translocated to the cell surface of the skeletal muscle cells, resulting in an increase in glucose uptake (Ploug and Ralston, 1998). However, the ratio of GLUT1:GLUT4 is higher in human myotubes compared to adult skeletal muscle (Sarabia, et al, 1992), resulting in a lower insulin responsiveness of glucose transport (Al-Khalili, et al, 2003, Sarabia, et al, 1992. Insulin typically increases glucose uptake by 40-50 % in myotubes (Aas, et al, 2002, Al-Khalili, et al, 2003, McIntyre, et al, 2004, Montell, et al, 2001.…”
Section: Glucose and Lipid Metabolismmentioning
confidence: 99%
“…It is also important to take notice of that glucose uptake in vivo is regulated by delivery, transport and metabolism (Rose and Richter, 2005), whereas cultured myotubes only allow studies of transport and metabolism. In these studies, another limitation to the myotube model is that compared to in vivo, the insulin-stimulated glucose uptake in primary human myotubes is relatively low (about 1.5-fold increased) , Al-Khalili, et al, 2003, McIntyre, et al, 2004, Montell, et al, 2001, possibly caused by a low expression of the insulin-responsive glucose transporter GLUT4 (Al-Khalili, et al, 2003, Sarabia, et al, 1992. In vivo, GLUT4 is more expressed in type 1 oxidative muscle fibers than type 2 fibers (Daugaard, et al, 2000, Gaster, et al, 2000, Stuart, et al, 2006, and insulin sensitivity correlates with the proportion of slow twitch oxidative fibers in the muscle (Lillioja, et al, 1987).…”
Section: Limitations Of the Myotube Modelmentioning
confidence: 99%
“…36 Myotubes were preincubated for 24 h in serum-free media depleted in insulin and containing 5.5 mM glucose. The cells were then incubated with or without the desired concentration of insulin (0-1 mM) for 45 min at 371C and then, rinsed once with glucose-free HEPES-buffered saline solution and subsequently incubated for 8 min with 10 mM 2-deoxy-[ 3 H]-glucose.…”
Section: Cell Analysismentioning
confidence: 99%